Electronic Filing System berbasis Electronic Leitz Ordner di PT. Taspen - Fharetsa Adrila; Desak Made Dharmawati (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
This paper intended to describe the implementation of electronic leitz ordner base of electronic filing system of PT Taspen (Incorporated) Secretariat Section. The main informants were: an assistant manager of archive depreciation; an executive staff of archive depreciation, and an executive staff of archive management. The qualitative descriptive research conducted for this research. Data acquired through participant observation, structures interviews, and document analysis. The resultshowed that the system supported by scanner hardware, compress and or reduce application software of “Orpalis”; Scanner software “scandAll PRO” and the main system “Electronic Leitz Ordner”. The stages of electronic filing system based on Electronic Leitz Ordner were (1) weeding the archive, to separate the archive from harmful things; (2) data recording (scanning) by scanner hardware’s aided by scanAll PRO software; (3) archive saving and recovering from computer internalsaving files and reducing and compressing application; (4) backing up the reduced data by efs elo application’ (5) sending backed archive manually from branches to center office, and; (6) archive depreciation by removing the archives to secretariat department; (7) archive extermination, and handover the archive to ANRI (National Archive Center of Indonesia).